Endophthalmitis following Intravitreal Injection, Cataract Surgery, and Vitrectomy: Clinical Features and Visual Outcomes - Ana Maria Cunha; Maria Manuel Iglésias; Amândio Rocha-Sousa; Fernando Falcão-Reis; Manuel Falcão (Journal of Ophthalmology)
Purpose. To describe and compare the clinical features and visual outcomes of endophthalmitis following intravitreal injections (IVI), cataract surgery, and pars plana vitrectomy (PPV). Methods. This is a single-centre, retrospective study. All included patients had acute postoperative endophthalmitis secondary to one of these three procedures. Visual acuity (VA), comorbidities, time to presentation, and treatment were assessed. The primary outcome was visual outcome. A poor outcome was considered if final VA was worse than or equal to counting fingers (CF) and a good outcome was classified as VA better than CF. Results. Over 12 years, a total of 61 patients were included. Twenty-seven cases were post-cataract endophthalmitis; twenty-five were post-IVI and nine post-PPV. Endophthalmitis post-PPV had a worse visual outcome (88.9% of patients with VA worse than or equal to CF 95% CI 51.3 to 100.0%) than endophthalmitis following cataract surgery (25.9% of patients with VA worse than or equal to CF 95% CI 11.0 to 39.9%) and the IVI subgroup (44.0% of VA worse than or equal to CF 95% CI 24.0 to 67.0%) (p=0.001 and p=0.047). There were no significant differences in the proportion of patients with a poor visual outcome between endophthalmitis following cataract surgery and IVI (p=0.171). Conclusions. The number of patients with poor visual outcomes following acute endophthalmitis was similar in endophthalmitis following IVI and cataract surgery, but better than endophthalmitis following vitrectomy.